Refinement of Outer Rotor Permanent Magnet Flux Switching Machine for Downhole Application - Khairul Fadzilah, Muhammad Fadhlan Hazim; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2025)
Electric machinery in downhole oilfield environments endure severe high-pressure, high-temperature (HPHT) conditions. This study examines a 12-slot/22-pole outer rotor Permanent Magnet Flux Switching Machine (PMFSM) optimized for these applications. JMAG Designer software was employed to model and simulate diverse combinations. A deterministic optimization method was utilized to enhance the design parameters, including rotor geometry, permanent magnet size, and coil turn quantity. The optimized model demonstrated a 102.6% augmentation in torque (from 16.58 Nm to 33.57 Nm), a diminution in cogging torque (from 3.2 Nm to 1.76 Nm), and a 37.3% reduction in magnet weight. These improvements validate the suitability of outer rotor PMFSMs for efficient and reliable downhole operations.